KEY ISSUES OF THE DEVELOPMENT OF PEDAGOGICAL EDUCATION IN STUDENTS - Mansurova Maftuna Ahatovna (Journal of new century innovations, 2023)
Abstract: Currently, when the process of globalization continues, it is important to respect universal values, to tolerate the customs, lifestyle, beliefs of our people. One of the topical problems of pedagogical science is the creation of the foundations of tolerance by means of national traditions in the minds of medical students these concepts. The more efficiently we use religious and secular ideas and teachings of morality, education, spirituality and education, developed over the centuries, the more reliable will be our national independence. One such effective exercises is the development of tolerance on the basis of national traditions.